2022
DOI: 10.1021/acsenergylett.2c01506
|View full text |Cite
|
Sign up to set email alerts
|

Slot-Die Coated Triple-Halide Perovskites for Efficient and Scalable Perovskite/Silicon Tandem Solar Cells

Abstract: Wide bandgap halide perovskite materials show promising potential to pair with silicon bottom cells. To date, most efficient wide bandgap perovskites layers are fabricated by spin-coating, which is difficult to scale up. Here, we report on slot-die coating for an efficient, 1.68 eV wide bandgap triple-halide (3halide) perovskite absorber, (Cs 0.22 FA 0.78 )Pb(I 0.85 Br 0.15 ) 3 + 5 mol % MAPbCl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 44 publications
5
40
0
Order By: Relevance
“…[55,56] For the reference stack, we measure an average PLQY of ≈1.26% corresponding to an implied V OC of 1.253 V, comparable to previously reported values for similar perovskite composition. [44,57] In line with the measured V OC statistics, the PLQY and implied V OC in case of evaporated 2PACz are slightly enhanced to average values of ≈1.7% and 1.261 V, respectively (Figure 2a,b). To obtain the internal ideality factor (n id ), we perform intensity-dependent PLQY measurement for the corresponding half-stacks and apply a fit to the calculated implied V OC as reported in our previous work.…”
Section: Photovoltaic Performance and Photophysical Propertiessupporting
confidence: 80%
“…[55,56] For the reference stack, we measure an average PLQY of ≈1.26% corresponding to an implied V OC of 1.253 V, comparable to previously reported values for similar perovskite composition. [44,57] In line with the measured V OC statistics, the PLQY and implied V OC in case of evaporated 2PACz are slightly enhanced to average values of ≈1.7% and 1.261 V, respectively (Figure 2a,b). To obtain the internal ideality factor (n id ), we perform intensity-dependent PLQY measurement for the corresponding half-stacks and apply a fit to the calculated implied V OC as reported in our previous work.…”
Section: Photovoltaic Performance and Photophysical Propertiessupporting
confidence: 80%
“…Compared with vacuum deposition technologies like multisource co-evaporation, the non-vacuum deposition technologies including spin-coating, slot-die coating, and blade coating have the advantages of low equipment cost, simple process, and low expected manufacturing cost. Among them, the slot-die coating has been proved to have high repeatability, good film quality, and other characteristics, which are particularly suitable for preparing a large-area polycrystalline perovskite film. …”
Section: Introductionmentioning
confidence: 99%
“…With a series of optimizations, they obtained a 2-terminal monolithic tandem solar cell with a champion PCE of 25.2% (active area 1 cm 2 ), which shows the high potential for slot-die coating as a fabrication route for industrially relevant perovskite/silicon tandem solar cells. 17…”
Section: Introductionmentioning
confidence: 99%
“…With a series of optimizations, they obtained a 2-terminal monolithic tandem solar cell with a champion PCE of 25.2% (active area 1 cm 2 ), which shows the high potential for slot-die coating as a fabrication route for industrially relevant perovskite/silicon tandem solar cells. 17 Most of the PSC efficiency records were supported by the use of organic hole-transporting materials (HTMs), such as 2,2 ′ ,7,7 ′tetrakis(N,N-di-p-methoxyphenylamine)9,9 ′ -spiro-biuorene (spiro-OMeTAD), poly(3-hexylthiophene) (P3HT) and polytriarylamine (PTAA). However, only a few studies demonstrated the compatibility of these materials with the large-scale solution fabrication process.…”
Section: Introductionmentioning
confidence: 99%